Prolapse of the Third Eyelid Gland in a Cat - da Silva Marques, Ana Beatriz; Fernandes Reiter, Luís Felipe; Martins Sandoval, Lívia; José Rosa Bueno, Vinícius; Baqui Dias, João Luis; Tatiany Pereira Kamimura, Irení; Prandini Simião Dias, Gabriela; Bertelis Merlini, Natalie (Acta Scientiae Veterinariae, 2024)
Background: The prolapse of the third eyelid gland is a condition that mainly affects dogs and is uncommon in cats. The diagnosis results from anamnesis and identification of a hyperemic mass in the medial corner of the eye bulb during ophthalmologic examination and may be accompanied by secretion and conjunctivitis. The treatment of choice is surgical repositioning of the 3rd eyelid gland. Several surgical techniques have been described, which can be divided into anchoring and pocket techniques. This study reports a case of 3rd eyelid gland prolapse in a cat with surgical resolution using the Morgan pocket technique. Case: A 7-year-old, female feline of undefined breed, weighing 6.5 kg, attended a private clinic in the city of Jundiaí, São Paulo. The owner informed scratching in the right eye after a contact fight with another feline. After the ophthalmologic exam, the only alteration found was in the 3rd eyelid, which presented intense chemosis and hyperemia. Treatment with eye drops containing neomycin sulfate, polymyxin B sulfate, dexamethasone, and 0.15% sodium hyaluronate was prescribed. In the 15-day follow-up, total regression of the chemosis and prolapse of the 3rd eyelid gland in the right eye was verified. Based on this scenario, it was decided that the 3rd eyelid gland should be repositioned. The Morgan pocket technique was chosen using 6-0 non-absorbable wire. In the postoperative period, tobramycin eye drops every 6 h, dexpanthenol ophthalmic gel 4 to 6 times a day for 10 days, and Elizabethan collar 24 h a day were prescribed. For analgesia, 25 mg/kg dipyrone and 0.05 mg/kg meloxicam with anti-inflammatory action were used orally once a day for 3 days. On the 11th day after surgery, the patient was reevaluated, and no ophthalmological changes were identified; the 3rd eyelid gland remained in its correct anatomical position. Discussion: Prolapse of the 3rd eyelid gland is a rare condition in cats. In the presented case, the macroscopic finding of this affection was a reddish mass located in the nasal corner of the ocular bulb, similar to the occurrence in dogs. In terms of age groups, the manifestation of this ophthalmopathy differs between the species and is present in puppies to young dogs, whereas adult to middle-aged cats. The occurrence of the disease is likely related to a genetic predisposition in dogs; in contrast, in cats, it may be related to ocular disturbances, such as conjunctivitis and trauma. In the literature, the cases of prolapse of this gland are mostly related to the Burmese breed; however, there are also descriptions for undefined breed and Persian cats. The etiology of gland prolapse in domestic cats remains unknown; changes in smooth muscle fibers that maintain the gland in its anatomical position, different from the hypothesis of laxity in the retinaculum of dogs is speculated. Using the Schirmer’s test in cats to evaluate the influence of the removal of the lacrimal 3rd eyelid gland, a study found a 15-26% decrease in the production of the aqueous portion of the tear film, providing additional support to the importance of gland repositioning. The Morgan pocket technique was selected for the present case based on the positive results when employed in dogs and cats. The invaginating suture and the positioning of the final knot performed in this technique avoid contact of the wire with the corneal surface and postoperative complications, such as ulcerative keratitis. The present report and the reviewed literature point out that the prolapse of the 3rd eyelid gland in cats may occur secondarily to an ocular disorder, such as trauma, and that the Morgan pocket technique is efficient for repositioning this gland in cats. Keywords: surgery, cat, ocular disturbance, Morgan pocket. Título: Prolapso da glândula da terceira pálpebra em uma gata Descritores: cirurgia, gato, alteração oftalmológica, Morgan pocket.